Ligand-specific conformational change drives interdomain allostery in Pin1 - Alexandra Born; Janne Soetbeer; Morkos A. Henen; Frauke Breitgoff; Yevhen Polyhach; Gunnar Jeschke; Beat Vögeli (Nature Communications, 2022)
Born et al. describe interdomain allostery in the two domain peptidyl-prolyl isomerase Pin1 upon binding of two ligands. These ligands couple population shifts of extended and compact states to changes in the catalytic site of Pin1.